A Regrettable Instance of Medical Abortion, How to Get-Going? - Baral, Josie; Rana, Ashma; Gurung, Geeta (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v6i1.5258 NJOG 2011; 6(1): 68